Effect of small quantities of potassium promoter and steam on the catalytic properties of nickel catalysts in dry/combined methane reforming. (19th January 2021) - Wysocka, Izabela; Mielewczyk-Gryń, Aleksandra; Łapiński, Marcin; Cieślik, Bartłomiej; Rogala, Andrzej
Abstract: Carbon dioxide and methane are two of the principal greenhouse gases. Reduction of their content in the atmosphere is currently the subject of much worldwide research. Dry and combined reforming of methane are effective methods of CO2 and CH4 utilization and production of synthesis gas (syngas) in chemical technology. Testing of catalysts that provide the desired H2 /CO ratio and long operation time is one of the critical aspects of syngas production and the focus of much study. In this study, K-promoted Ni/MgAl2 O4 catalysts prepared using a co-precipitation-impregnation method with different K/Ni ratios (range of 0–0.15) were examined in dry reforming of methane (DRM). The obtained catalysts were characterized using X-ray diffractometry (XRD), atomic emission spectrometry (MP-AES), Brunauer–Emmett–Teller (BET) specific surface area, BJH pore size distribution, TEM imaging, analysis of reducibility H2 -TPR, infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Hammet basicity analysis, thermogravimetric analysis (TG) and elemental carbon-hydrogen-nitrogen analysis (CHN). Promotion of nickel catalysts with potassium led to changes in nickel distribution, metal-support interactions and deceleration of carbon deposition while enhancing sorption of carbon dioxide and reduction of nH2:CO to 0.5 for 0.7 K–Ni/MgAl2 O4 catalyst. To obtain the required H2 :CO ratio close to unity a study on the effect of steam in inlet stream was performed. It was found that maintaining inlet stream composition equal CH4 :CO2 :H2 O = 1.0:1.0:0.1 obtained an H2 :CO ratio close to unity. Graphical abstract: Image 1 Highlights: Small quantities of potassium significantly improved anti-coking properties. Potassium at low content strongly affects morphology and activity of catalysts. Negative effect of increased MgAl2 O4 basicity on H2 /CO ratio. Adjustable H2 /CO ratio due to introduction of a small steam content.